Analisis Postur Tubuh Departement Welding Dengan Metode RULA Studi Kasus Di PT SMT - Masifora, Aji; Nugraha, Asep Erik (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT.SMT is a company engaged in processing and assembling products from sheet metal materials, in the production process some processes are still conventional. According to the initial assessment, welding and grinding stations are two workstations where operators often experience injuries. The study's objective was to assess the operator's working position in order to gauge the severity of a work injury. The technique is called RULA (Rapid Upper Limb Assessment). Four operators are at a high risk, as shown by the NBM (Nordic Body Map) computations. These operators work in the welding process, which receives scores of 73 and 69, and the grinding process, which receives scores of 60 and 64.. The score of 6 is obtained from the RULA score for the operator's welding process in the welding department, indicatingng that more research needs to be done and change needs to happen quickly. This shows that to reduce operator work accidents, the production process must be improved.